Bank Keliling Function for Society at Pasir Ipis Lembang in West Bandung Districts - Adinda Prissilia; Wahju Gunawan; Ahmad Buchari (International Journal of Social Sciences Review, 2022)
In this research, author took the case of Bank Keliling function for society at Pasir Ipis Lembang. Bank Keliling is one of business entity that provide loans to people in the form of credit. The practice of Bank Keliling due to economy conditions society having income be inadequate to fulfill life need. Pasir Ipis Lembang is one of the village is in the village Jayagiri Bandung regency west where Bank Keliling system is a business entities that are attractive to people because of the villages that are distant from urban and living standard remain low make the community had no choice and the community borrowed through Bank Keliling system. The theory of functionalism structural Merton, there are manifest function and latent function who become review for an author in analyze research. The author use the qualitative method with descriptive analysis. The data obtained from the results of the collection of primary data and also secondary data by interviews. Data obtained form the results of the interview noted and collected. All the data obtained analyzed qualitatively so as to what lies behind such a reality can be unearthed. The result of research is that manifest function of Bank Keliling on community increase business capital of accessibility given a Bank Keliling while latent function through high interest and the Bank Keliling who did the violence when their billing loans. The conclusion of the research is that Bank Keliling having the function to community.